Optimization of soil acidification in landfill using wood ash / Fatihah Abdullah - Abdullah, Fatihah (Faculty of Applied Sciences, 2016)
One of the characteristic of landfill soil is either in acidic condition or alkaline condition. The pH value for this soil is depends on several factors, for example soil type, or type of garbage that gathered together in one place, that could be produced the acidic and alkaline. Wood ash was used in this experiment, which is can be function as a medium to optimize the soil acidification. Two types of wood ash, which are Acacia mangium willd sp and Endospermum malaccensa sp was tested to see how far this wood ash can minimize the pH value of acidic landfill soil. In early step, distilled water and calcium chloride (CaCl2) were used to determine the soil pH, and then following by using the wood ash. Two methods were applied in this experiment. First analysis is FTIR, which is to detect the components in wood ash. Second analysis is pH meter, which is to check soil pH. In this study, 0.1% to 0.5% weight of wood ash has been applied on each soil sample and based on the obtained result, 0.1% weight of wood ash that had been applied in this experiment, was chosen as the best weight to optimize the acidic soil, compare to others four percentage weight of wood ash due to its ability to neutralize the landfill soil, reaching 7, which mean neutral in pH graph